Strengthening School Branding through Mentoring-Based Development of a Profile Video and Website at MIM Semanu (ABDIMAS: Jurnal Pengabdian Masyarakat, 2026)
The rapid development of digital technology requires educational institutions to strengthen their institutional image and competitiveness through effective digital media. Madrasah Ibtidaiyah Muhammadiyah (MIM) Semanu, Gunungkidul, had not yet possessed representative digital media to support school branding and information dissemination. This Community Service Program aimed to strengthen school branding through mentoring-based development of a school profile video and an official school website. The program was implemented through preparation, training, mentoring, media production, and evaluation stages. The mentoring process emphasized capacity building for teachers and school administrators to independently manage digital branding media. The program resulted in the successful production of a school profile video and the establishment of an official school website as sustainable branding tools. Quantitative evaluation showed an increase in participants’ mean scores from 4.43 in the pre-test to 4.90 in the post-test, indicating improved understanding and skills in digital media management. These findings demonstrate that mentoring-based community service effectively enhances both digital outputs and human resource capacity for sustainable school branding, particularly in Islamic primary education contexts.